Analisis Efisiensi Dan Efektivitas Penerapan Fire Safety Management Dalam Upaya Pencegahan Kebakaran di PT. Consolidaetd Electric Power Asia (Cepa) Kabupaten Wajo - Husnul Khatimah Muchtar; Hasbi Ibrahim; Sitti Raodhah (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2016)
Potential fire hazards can occur in any sector with various impacts such as threatening the safety and health of workers, be materially adversely affected by social. From some potential fire hazards showed a need to improve awareness of fire prevention. One effort that can be done is through better management. This study aims to determine the efficiency and effectiveness of the Fire Safety Management (FSM) application in the fire prevention efforts in PT. CEPA Wajo. This research is quantitative descriptive approach to the population is the FSM program. The sample in this study is the management policy, organization, identification of the fire risk, coaching and training, and inspection of fire protection facilities. As for the respondents in this study were two workers in the QEHS Department. The results showed that the application of the FSM program at PT. CEPA Wajo Regency 2015 is implemented fairly efficiently and effectively with a percentage of 83.6%. Management policies are efficiently and effectively (97.5%), inspection of fire protection systems is fairly efficiently and effective (84.5%), risk identification is fairly efficient and effective (84%), the organization is less efficient fire and effective (75%), as well as coaching and training are less efficient and effective (77.3%). We recommend that the management needs to monitor and evaluate the Fire Safety Management program periodically so that the program can be implemented more efficiently and effectively. Keywords : Efficiency, Effectiveness, Fire Safety Management